1976
DOI: 10.1021/bi00663a001
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium dependence of the association kinetics of Escherichia coli ribosomal subunits

Abstract: The magnesium dependence of the Escherichia coli ribosomal subunits association has been investigated by the stopped-flow technique using isolated 30S and 50S particles depleted of polyamines and any initiation factor. Binding of the fluorescent probe bis(8-anilino-1-naphthalenesulfonate) to the ribosomal proteins occurs through biphasic kinetics. A dark reaction corresponding to a very rapid, reversible complexation of the dye molecule is followed by a slow photochemical reaction that gives rise to irreversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Because efficient extraction of membrane-bound polysomes requires detergent (Potter and Nicchitta, 2002), we expected cytoplasmic species to predominate in our lysates. Although Mg 2+ concentrations up to 30 mM are often used when preparing yeast extract for polysome profiling (Bhattacharya et al, 2010), [Mg 2+ ] in excess of 8 mM can drive vacant couple formation (Favaudon and Pochon, 1976); therefore, we limited total [Mg 2+ ] to 5 mM in all experiments.…”
Section: Monosome Polysome and Global Footprintingmentioning
confidence: 99%
“…Because efficient extraction of membrane-bound polysomes requires detergent (Potter and Nicchitta, 2002), we expected cytoplasmic species to predominate in our lysates. Although Mg 2+ concentrations up to 30 mM are often used when preparing yeast extract for polysome profiling (Bhattacharya et al, 2010), [Mg 2+ ] in excess of 8 mM can drive vacant couple formation (Favaudon and Pochon, 1976); therefore, we limited total [Mg 2+ ] to 5 mM in all experiments.…”
Section: Monosome Polysome and Global Footprintingmentioning
confidence: 99%
“…It also reduces the electrostatic repulsion between the subunits by masking the charges on the rRNA [25]. In both prokaryotes and mitochondria, spermine has been shown to tighten the interaction between the ribosomal subunits [15,26].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the equilibrium between 70 S ribosomes and the 30 S and 50 S subunits is influenced by polyamines (21,22). In the presence of 2-3 mM Mg 2ϩ and 100 mM K ϩ , however, the percentage of 70 S ribosomes (70 -80% of total ribosomes) was not influenced strongly by 0.5-1 mM spermidine (data not shown).…”
Section: Determination Of the Size Of Oppa Mrna Is Necessary For The mentioning
confidence: 99%